2016
DOI: 10.1071/he16057
|View full text |Cite
|
Sign up to set email alerts
|

Reach, engagement, and effectiveness: a systematic review of evaluation methodologies used in health promotion via social networking sites

Abstract: Issue addressed Social networking sites (SNS) are increasingly popular platforms for health promotion. Advancements in SNS health promotion require quality evidence; however, interventions are often not formally evaluated. This study aims to describe evaluation practices used in SNS health promotion. Methods A systematic review was undertaken of Medline, PsycINFO, Scopus, EMBASE, CINAHL Plus, Communication and Mass Media Complete, and Cochrane Library databases. Articles published between 2006 and 2013 describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 64 publications
1
59
0
2
Order By: Relevance
“…As the materials are discussed, debated and generated by the users, the evolved (co‐created) outcomes will be evaluated according to their value and worth for each segment. The user generated outcomes will be evaluated in an online survey to the same participants (n = 100) which will also produce analytics for engagement and effectiveness of the co‐created SM campaigns . Young Aboriginal adults will be included in the same co‐creation activity and will be recruited by the Aboriginal researcher (TW).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the materials are discussed, debated and generated by the users, the evolved (co‐created) outcomes will be evaluated according to their value and worth for each segment. The user generated outcomes will be evaluated in an online survey to the same participants (n = 100) which will also produce analytics for engagement and effectiveness of the co‐created SM campaigns . Young Aboriginal adults will be included in the same co‐creation activity and will be recruited by the Aboriginal researcher (TW).…”
Section: Methodsmentioning
confidence: 99%
“…The user generated outcomes will be evaluated in an online survey to the same participants (n = 100) which will also produce analytics for engagement and effectiveness of the co-created SM campaigns. 78 Young Aboriginal adults will be included in the same co-creation activity and will be recruited by the Aboriginal researcher (TW).…”
Section: Methodsmentioning
confidence: 99%
“…depression and anxiety ); however, such data are often poorly reported or absent from primary studies. Advanced web analytical tools now provide researchers with opportunities to capture metrics that could approximate intervention adherence and engagement, including length of time spent browsing a page, video views, comments, shares, likes and re‐posts that could be utilized in future trials.…”
Section: Declaration Of Interestsmentioning
confidence: 99%
“…This is particularly important given that, as the authors note, five of the 17 included studies used completer‐only analyses. It has been suggested that some of the benefits of internet interventions, including anonymity and self‐directed learning, may actually facilitate high participant attrition . For example, the authors of one study noted that participants could simply close their web browsers once the questionnaires appeared on screen.…”
Section: Declaration Of Interestsmentioning
confidence: 99%
“…mación relativa a esta materia tengan un mayor protagonismo (Parikh y Huniewicz, 2015) y que profesionales y pacientes puedan relacionarse de manera más directa. Este nuevo panorama ha llamado también la atención del mundo académico, de manera que las investigaciones sobre redes sociales y salud han proliferado en los últimos años, hasta el punto de que los autores que se han dedicado a analizar la bibliografía existente han localizado más de un centenar de trabajos de estas característi-cas (Moorhead et al, 2013;Amon et al, 2014;Koteyko, Hunt y Gunter, 2015;Veneroni et al, 2015;Lim et al, 2017).…”
Section: Palabras Claveunclassified